Wisdom is A Tree of Life (Prov. 3:18): A Conceptual Metaphor: Hikmat adalah Pohon Kehidupan (Ams. 3:18): Sebuah Metafora Konseptual - Dirgaprimawan, Bernadus (STF Driyarkara - Diskursus, 2023)
This article examines a proverbial saying